2019
DOI: 10.3389/fmicb.2019.01642
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Unusual Properties of the Master Regulator FNR in the Extreme Acidophile Acidithiobacillus ferrooxidans

Abstract: The ability to conserve energy in the presence or absence of oxygen provides a metabolic versatility that confers an advantage in natural ecosystems. The switch between alternative electron transport systems is controlled by the fumarate nitrate reduction transcription factor (FNR) that senses oxygen via an oxygen-sensitive [4Fe-4S] 2+ iron-sulfur cluster. Under O 2 limiting conditions, FNR plays a key role in allowing bacteria to transition from aerobic to anaerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 80 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…Also, this molecule is a co-factor for ArxA too (Zargar et al, 2010). Besides, the presence of the transcriptional fumarate and nitrate reductase regulator fnr in this genetic cluster could be evidence of an anoxic related response (Osorio et al, 2019). Finally, as most of our studied markers are part of the core genome compartment, we would imply that differences in regulation and expression levels among the strains could be the source of their variable arsenic tolerance levels.…”
Section: A B Cmentioning
confidence: 90%
“…Also, this molecule is a co-factor for ArxA too (Zargar et al, 2010). Besides, the presence of the transcriptional fumarate and nitrate reductase regulator fnr in this genetic cluster could be evidence of an anoxic related response (Osorio et al, 2019). Finally, as most of our studied markers are part of the core genome compartment, we would imply that differences in regulation and expression levels among the strains could be the source of their variable arsenic tolerance levels.…”
Section: A B Cmentioning
confidence: 90%
“…The abundancy of signal transduction mechanisms generally declines with decreasing genome size, as it has been found that the number of one- and two-component signal transduction systems is proportional to the square of the genome size ( Konstantinidis and Tiedje, 2004 ; Galperin, 2005 ; Ulrich et al, 2005 ). Extensive research has been conducted on the different signal pathways and regulatory networks of acidophiles ( Rzhepishevska et al, 2007 ; Shmaryahu et al, 2009 ; Moinier et al, 2017 ; Díaz et al, 2018 ; Osorio et al, 2019 ). However, additional research is needed to uncover what signal pathways are not present in these organisms.…”
Section: Resultsmentioning
confidence: 99%
“…This would create pressure for strains to rapidly demonstrate their effectiveness to their legume host. Past work has suggested that one of the benefits of FnrN compared to FixLJ-FixK is that it is more responsive to O 2 concentration, providing more flexible regulation [ 86 , 87 , 128 ]. By enabling more fine-tuned control, integrated multi-sensor O 2 regulatory pathways may speed up the symbiotic transition, providing a competitive advantage.…”
Section: Discussionmentioning
confidence: 99%